The role of neoadjuvant chemoradiotherapy in multimodality treatment of esophageal or gastroesophageal junction cancer - Klevebro, Fredrik; Nilsson, Magnus (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
The issues raised by Stiles and Altorki in the editorial on our trial NeoRes are important and deserve in depth discussion and further study (1). We agree with Stiles and Altorki that there is currently no scientific basis at all for considering neoadjuvant chemoradiotherapy to be in any way superior to chemotherapy alone and as they point out there is some evidence that the addition of radiation increases postoperative morbidity and mortality without adding a long-term survival benefit for esophageal adenocarcinomas. Esophageal cancer is still a relatively rare condition, at least in Western populations, and it is difficult and expensive to perform large prospective studies. The scientific evidence for combination therapies is based on relatively small and heterogeneous RCTs. Furthermore there is evidence suggesting that the generalization of the results from trials to all patients have led to an overtreatment of unfit, co-morbid patients with perioperative oncological therapy (2) as the patients who are included in the trials are not representative of the average patient. Future studies need to focus on patient selection based on ability to tolerate treatment, frailty and tumor phenotype, enabling a finer granularity in the tailoring of treatment to individual patients.